Intelligent Multi-verse-based Fuzzy Optimization for LFC Model - P Srividyadevi, Rekha M, G. Sandya Rani, M.N. Sandya Rani, J. Sridevi (International Journal of Advanced Science and Technology, 2020)
Load frequency Problem is one of the most important issue in the area of the Power System. A four-area interconnected hybrid power plant is considered for the performance analysis w.r.to the controllers. Here in this proposed paper, the combined combination of the optimization with the intelligent controlling techniques are cast-off to see the performance on the system. Multiverse Optimizastion(MVO) along with Fuzzy logic controllers(FLC) are used for the analyzing the performance of the four-area hybrid thermal power plant. Thus, form MVO-Fuzz technique to analyse the performance of the change in frequency deviations at certain operating scenario.